2022
DOI: 10.1021/acsanm.2c03916
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized MXene Nanosheets and Al-Doped ZnO Nanoparticles for Flexible Transparent Electrodes

Abstract: Transparent, flexible, and chemically stable conducting electrodes are the most important key components for fabricating optoelectronic devices. However, in conventional bulk metal−semiconductor (MS) junctions, Fermi-level pinning is a major concern that limits the charge transport properties of the devices. In this work, we have designed MS junctions using twodimensional (2D) MXene nanosheets and Al-doped ZnO nanoparticles as a metal and an n-type semiconductor, respectively. The heterojunction was formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The tunneling current and d I /d V versus sample bias of the nanosheets and the clusters are presented in Figure e,f and Figure S8. From the I – V characteristics and the corresponding d I /d V spectrum in Figure e,f (black) the pristine Ti 3 C 2 nanosheet samples exhibited semimetallic nature with zero DOS slightly shifted to 0.04 V from the Fermi level ( E F ) of the substrate electrode . The zero DOS position is called the Dirac point of the MXene where the VB and CB bands meet in a single point .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tunneling current and d I /d V versus sample bias of the nanosheets and the clusters are presented in Figure e,f and Figure S8. From the I – V characteristics and the corresponding d I /d V spectrum in Figure e,f (black) the pristine Ti 3 C 2 nanosheet samples exhibited semimetallic nature with zero DOS slightly shifted to 0.04 V from the Fermi level ( E F ) of the substrate electrode . The zero DOS position is called the Dirac point of the MXene where the VB and CB bands meet in a single point .…”
Section: Resultsmentioning
confidence: 99%
“…), Ti 3 C 2 T x MXene is the most popular 2D material because of its easy delamination into a monolayer by HF treatment, which can help to explore the real 2D characteristics of MXene. Pristine Ti 3 C 2 MXene is expected to form a Schottky junction with semiconductors, which is usually formed at the semiconductor–metal interface by utilizing the difference in the work function of metal and semiconductor. Several studies showed that conductive Ti 3 C 2 MXene can effectively promote the photocatalytic performance of TiO 2 , ZnO, CeO 2 , g-C 3 N 4 , CdS, Bi 2 S 3 , and ternary semiconductors by superior interface engineering. The enhanced catalytic activity of TiO 2 is mainly due to the efficient separation of charge carriers at the heterojunctions formed between Ti 3 C 2 T x and TiO 2 . , Unlike conventional metallic materials, 2D Ti 3 C 2 MXene used as a gas-sensing metal reveals excellent performance by modulation of in situ-built Ti 3 C 2 –TiO 2 Schottky barriers within the sensing channel. Likewise, the rutile TiO 2 nanoparticles obtained from Ti 3 C 2 MXene oxidations are proven to be beneficial for the electron transporting layer in perovskite solar cells owing to their excellent defect and trap-assisted recombination suppression properties at the interface. , …”
Section: Introductionmentioning
confidence: 99%
“…Holes are also moved to the MXene matrix in MXBZ as MXene always acts as a charge trapper, and more charges are accumulated in the interface of the photocatalyst. 51 So, the life span of the electron-hole pair is increased due to the formation of multiple junctions in the ternary MXBZ photocatalyst. These interfacial charges create more active radicals, which can break the dye molecules in the photocatalysis process.…”
Section: Photocatalytic Activity Of Mxbzmentioning
confidence: 99%
“…Besides these combinations, there are other hybrid materials like 1D/2D hybrid nanomaterials, metal-metal hybrid materials, metal-polymer combinations, 2D nanomaterial/polymer, etc., used in FTCEs. [37,91,118,120,200,383,384]…”
Section: Other Hybrid Materials-based Ftcesmentioning
confidence: 99%